Mystifying the Monarch Studies on Discourse, Power, and History - Deploige, Jeroen; Deneckere, Gita (Amsterdam University Press, 2006)
The history of kings and queens has always appealed to popular imagery. Monarchy is also a central theme to classic surveys of political history. The present volume approaches the relation between imagery and authority of the monarchy from a cultural historical angle. The authors focus on the different discourses produced since the Middle Ages aiming at the symbolic construction of royal power in Western Europe, as well as at its subversion. The history of monarchy is not a linear process from sacralization to banalization. Throughout premodern, modern and postmodern times, the mystification and demystification of the monarch remain inextricably intertwined. This title is available in the OAPEN Library - http://www.oapen.org.